Which One is More Attractive to Traveler, Taxi or Tailored Taxi? An Empirical Study in China. (2016) - Zhang, Yujie; Guo, Hongwei; Li, Cheng; Wang, Wuhong; Jiang, Xiaobei; Liu, Yang
Abstract: Apart from public transit, urban citizens nowadays seek for the personalized travel mode more frequently to satisfy their ever-increasing travel demand. Tailored taxi, based on mobile internet technology, such as Uber in America and Didi-taxi in China, characterizing by its high quality service, is now rapidly expanding its market penetration worldwide. The new emerging tailored taxi challenges the conventional taxi industry. This study concentrates on the personalized travel choices between taxi and tailored taxi. The personalized travel choice is determined by personal characteristic and trip characteristic. Using stated preference technique, a questionnaire is design to acquire data on travel preference. Then the binary logit model is proposed to describe the preferences of traveler's personalized travel behavior. Next, the sensitivity analysis is performed to discuss the influence of different preference factors and individual's characteristics. Finally, the general features of taxi and tailored taxi users are described and the differential development strategies are proposed.